IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAH (SAP) BERBASIS AKRUAL DI INDONESIA - Trisnawati, Novi (Manajemen & Bisnis Jurnal, 2019)
Accrual-based accounting system is a modern accounting system that is widely applied in developed countries. While Indonesia has been using an accrual-based accounting system in the private sector for a long time. however, for the government sector, before 2010 Indonesia still used cash basis and cash toward accrual basis. But after the issuance of PP 71 of 2010 all government sectors are required to use an accrual basis to prepare their financial statements. The application of the accrual basis is expected to be able to improve the performance of government units. This improvement will be demonstrated by the better opinion obtained on financial statements, both LKPP and LKKL. And the improved opinion obtained will increase public confidence in the government regarding the use of funds that have been obtained from them. Therefore, for the implementation of accrual basis accounting to be fully implemented, several requirements are needed, including: (1) Improvements that must be made to an adequate accounting system and accounting technology, including a reliable internal control system; (2) The availability of competent accountants as adequate HR requirements; (3) Appropriate strategies are used for applying the accrual basis; (4) political commitment; and (5) communicating the purpose of applying this basis. Keywords: government accounting standard, accrual based accounting